2016
DOI: 10.15420/aer.2016.14.2
|View full text |Cite
|
Sign up to set email alerts
|

Post-extrasystolic Blood Pressure Potentiation as a Risk Predictor in Cardiac Patients

Abstract: In 1885, Oscar Langendorff was the first person to describe the increase in contractility ('Pulsverstärkung') that follows an extrasystole.1 Langendorff experimented with spontaneously beating isolated frog hearts. He recorded the heartbeats by using a lever that transferred the contractile movements of the heart to a rotating drum. Electrical stimulation resulted in premature contractions that were followed by compensatory pauses. In these experiments, he noticed that myocardial contractility during the first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…During the post-extrasystolic beat, RyRs have recovered from inactivation, and then increased intracellular calcium stores are released from these channels, resulting in increased contractility [ 73 ]. Previous studies found a significant increase in PESP in heart failure patients, and suggested that PESP could serve as a risk predictor of cardiac dysfunction and a prognostic indicator for patients with myocardial infraction [ 73 , 74 ]. Increased PESP is associated with abnormal calcium cycling induced by heart failure.…”
Section: The Risk Factors For Developing Pvicmmentioning
confidence: 99%
“…During the post-extrasystolic beat, RyRs have recovered from inactivation, and then increased intracellular calcium stores are released from these channels, resulting in increased contractility [ 73 ]. Previous studies found a significant increase in PESP in heart failure patients, and suggested that PESP could serve as a risk predictor of cardiac dysfunction and a prognostic indicator for patients with myocardial infraction [ 73 , 74 ]. Increased PESP is associated with abnormal calcium cycling induced by heart failure.…”
Section: The Risk Factors For Developing Pvicmmentioning
confidence: 99%
“…Furthermore, the reduction in LVET after standing is smaller in HF patients [ 260 ]. Third, the increase in cardiac contractility after a prolonged beat (due to an extrasystolic beat or AF) is greater in HF patients [ 261 ]. Outstanding research questions include: 1) which metrics are predictive of incident HF and 2) what thresholds should be used to identify patients who warrant screening for HF?…”
Section: Clinical Applicationsmentioning
confidence: 99%